PERENCANAAN FONDASI TIANG PANCANG PADA GEDUNG BLOK A JAYA PASAR RAYA PADANG DAN POTENSI TERJADINYA LIKUEFAKSI - Agus, Agus; Muchlian, Meli; Alfurqon Zaki, Fikky (Ensiklopedia of Journal, 2025)
In building planning, it is necessary to consider the potential for earthquake and liquefaction disasters in the area. Earthquake and liquefaction events can cause failure of the upper and lower structures of the building due to the soil losing/decreasing its bearing capacity. This study takes a case study of foundation planning in the construction of Block A Jaya Pasar Raya Padang Building, where the initial planning type of foundation used was a vertical dowel concrete rib net foundation (JEB). In this study, the foundation was replaced with precast piles. The study was to determine the bearing capacity and settlement of single and group pile foundations and calculate the potential for liquefaction disasters when an earthquake occurs. The methods used were the Meyerhoff method (1976) to obtain the bearing capacity of pile foundations, the Vesic method (1969) for the amount of settlement, and the Seed and Idriss method (1971) for the liquefaction potential. The study results showed that the soil did not have the potential for liquefaction up to a depth of 39 meters. The settlement amount in the pile group foundation is 9.00 mm <10 mm from the settlement permit based on SNI 8460-2017 Geotechnics (9.2.5.3), and the bearing capacity for the pile group is 2453.15 tons. It can be concluded that the Block A Jaya Pasar Raya Padang Building uses a pile foundation at a depth of 39 m, and the soil does not have the liquefaction potential or is safe.Keywords: pile foundation, liquefaction, bearing capacity